BioAdhere: tailor-made bioadhesives for epiretinal visual prostheses. (18th May 2022) - Hintzen, Kai-Wolfgang; Simons, Christian; Schaffrath, Kim; Roessler, Gernot; Johnen, Sandra; Jakob, Felix; Walter, Peter; Schwaneberg, Ulrich; Lohmann, Tibor
Abstract : The BioAdhere study: biocompatible, tailor-made bioadhesive peptides (peptesives) fixating macroscopic objects on the retinal surface. Abstract : Introduction : Visual prostheses, i.e. epiretinal stimulating arrays, are a promising therapy in treating retinal dystrophies and degenerations. In the wake of a new generation of devices, an innovative method for epiretinal fixation of stimulator arrays is required. We present the development of tailor-made bioadhesive peptides (peptesives) for fixating epiretinal stimulating arrays omitting the use of traumatic retinal tacks. Materials and methods : Binding motifs on the stimulating array (poly[chloro- p -xylylene] (Parylene C)) and in the extracellular matrix of the retinal surface (collagens I and IV, laminin, fibronectin) were identified. The anchor peptides cecropin A (CecA), KH1, KH2 (author's initials) and osteopontin (OPN) were genetically fused to reporter proteins to assess their binding behavior to coated microtiter plates via fluorescence-based assays. Domain Z (DZ) of staphylococcal protein A was used as a separator to generate a bioadhesive peptide. Following ISO 10993 "biological evaluation of medical materials", direct and non-direct cytotoxicity testing (L-929 and R28 retinal progenitor cells) was performed. Lastly, the fixating capabilities of the peptesives were tested in proof-of-principle experiments. Results : The generation of the bioadhesive peptide required evaluation of the N- and C-anchoring of investigated APs. The YmPh–CecA construct showed the highest activity on Parylene C in comparison with the wildtype phytase without the anchor peptide. eGFP–OPN was binding to all four investigated ECM proteins (collagen I, laminin > collagen IV, fibronectin). The strongest binding to collagen I was observed for eGFP–KH1, while the strongest binding to fibronectin was observed for eGFP–KH2. The selectivity of binding was checked by incubating eGFP–CecA and eGFP–OPN on ECM proteins and on Parylene C, respectively. Direct and non-direct cytotoxicity testing of the peptide cecropin-A–DZ–OPN using L-929 and R28 cells showed good biocompatibility properties. Proof-of-concept experiments in post-mortem rabbit eyes suggested an increased adhesion of CecA–DZ–OPN–coated stimulating arrays. Conclusion : This is the first study to prove the applicability and biocompatibility of peptesives for the fixation of macroscopic objects.